Struktur Komunitas Fitoplankton di Danau Toba, Sumatera Utara - Arif Rahman; Niken Tunjung Murti Pratiwi; Sigid Hariyadi (Institut Pertanian Bogor, 2016)
Lake Toba is the largest lake in Indonesia, located in the Province of North Sumatra. Lake Toba is used to aquaculture, agricultural, tourism, and residential areas. These activities will produce organic and anorganic matter that can affect water quality and can cause eutrophication. Some indicators of eutrophication are an increase in phytoplankton biomass and changes in phytoplankton community structure. The aim of this study was to describe the phytoplankton community structure in Lake Toba. This study was conducted on 20-24 October 2014 at 23 stations around the Samosir Island, Lake Toba. The results showed that the phytoplankton abundance ranged 216-68.319.716 cells/m3. The phytoplankton composition consists of 35 genera from four classes: Cyanophyceae, Chlorophyceae, Bacillariophyceae, and Dinophyceae. Chyanophyceae is a dominant phytoplankton groups based on the composition of abundance (>40%). Structure of phytoplankton communities in Lake Toba dominated by Anabaena.